Proceedings of the 2008 ACM Symposium on Virtual Reality Software and Technology 2008
DOI: 10.1145/1450579.1450615
|View full text |Cite
|
Sign up to set email alerts
|

Use of auditory cues for wayfinding assistance in virtual environment

Abstract: This paper addresses the crucial problem of wayfinding assistance in the Virtual Environments (VEs). A number of navigation aids such as maps, agents, trails and acoustic landmarks are available to support the user for navigation in VEs, however it is evident that most of the aids are visually dominated. This work-in-progress describes a sound based approach that intends to assist the task of 'route decision' during navigation in a VE using music. Furthermore, with use of musical sounds it aims to reduce the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…A proposed solution for this type of cognitive overload is to reallocate some of the information presented to the user from the visual stimuli to auditory stimuli (Mayer &Moreno, 2003). For example, while the user engages in a visual search task of the VE, they might use an auditory navigational tool, such as the musical tool for navigation proposed by Dodiya and Alexandrov (2008). Further research could be done to explore the use of auditory versus visual types of navigational tools for tasks other than navigation.…”
Section: Discussionmentioning
confidence: 99%
“…A proposed solution for this type of cognitive overload is to reallocate some of the information presented to the user from the visual stimuli to auditory stimuli (Mayer &Moreno, 2003). For example, while the user engages in a visual search task of the VE, they might use an auditory navigational tool, such as the musical tool for navigation proposed by Dodiya and Alexandrov (2008). Further research could be done to explore the use of auditory versus visual types of navigational tools for tasks other than navigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the sound was only audible on a specific range around the landmark. Other studies used acoustic beacons, which are sound cues used for navigation tasks, for wayfinding that is either continuous [Dodiya and Alexandrov 2008;Tran et al 2000] or noncontinuous [Walker and Lindsay 2003;Lokki et al 2000;Tran et al 2000]. Tran et al showed that a continuous versus pulsed beacon sound did not affect the overall localization accuracy, and participants preferred a continuous beacon sound over a pulsed sound [Tran et al 2000].…”
Section: Overview and Related Workmentioning
confidence: 99%
“…Short bursts of non-speech auditory information (earcons) were developed. Similar to tactons, earcons have been shown to aid exploration of graphical user interfaces, support navigation in menu hierarchies, and assist users in mobile wayfinding applications (Brewster, 1998;Brewster et al, 1995;Doyiya and Alexandrov, 2008). We also examined low-cost methods of amplifying vibrations, described in more detail in Section 4.3.1.…”
Section: Improving Perception Of Tactile Informationmentioning
confidence: 99%